Réponses

Meilleure réponse !
2013-05-06T20:43:51+02:00

Bonjour,

 

cela donne : 3*3/4*3 + 1*4/3*4

                               SUR

                             2 - 7/3

 

A = 9/12 + 4/12

        SUR

     2/1 - 7/3 

 

A = (9+4) /12

        SUR

    6/3 - 7/3

 

A= 13/12

     SUR

   -1 sur 3

 

Ce qui donne -13/4

 

Voilà 

2013-05-06T20:44:23+02:00

1er cacul: Tu dois dois mettre les dénominateurs au même nombre

= 3*3/4*3+1*4/3*4

=9/12+4/12

=13/12

 

2e calcul

= 2/1-7/3

= 2*3/1*3-7/3

=6/3-7/3

=13/3